2017
DOI: 10.1021/acsami.6b15408
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylidene fluoride) Containing Phosphonic Acid as Anticorrosion Coating for Steel

Abstract: Vinylidene fluoride (VDF)-based copolymers bearing pendant phosphonic acid function for potential application as anticorrosion coatings were synthesized via free radical copolymerization of VDF with a new phosphorus containing 2-trifluoromethacrylate monomer, (dimethoxyphosphoryl)methyl 2-(trifluoromethyl)acrylate (MAF-DMP). MAF-DMP was prepared from 2-trifluoromethacrylic acid in 60% overall yield. Radical copolymerizations of VDF with MAF-DMP initiated by tert-amyl peroxy-2-ethylhexanoate at varying ([VDF]/[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 69 publications
1
52
0
Order By: Relevance
“… Synthesis of different functional 2‐trifluoromethacrylates (MAF‐esters) from 2‐trifluoromethacrylic acid and their radical copolymerizations for specific materials …”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“… Synthesis of different functional 2‐trifluoromethacrylates (MAF‐esters) from 2‐trifluoromethacrylic acid and their radical copolymerizations for specific materials …”
Section: Applicationsmentioning
confidence: 99%
“…[20,21] Scheme2.Synthesis of different functional 2-trifluoromethacrylates (MAFesters) from 2-trifluoromethacrylic acid andtheir radical copolymerizations for specific materials. [23][24][25][26][27] Figure 2. Original Lumiflon (X = Cl) or Zeffle (X = F) resins/paintsb ased on an alternatedstructure containingC TFE or TFE and functional vinyl ether units.…”
Section: Coatingsmentioning
confidence: 99%
“…Using functional monomers to copolymerize VDF allows control over the spatial distribution of the comonomers in the polymer backbone, while having easily crosslinkable functional groups. [24][25][26] In this way, changes in the material color or chain scission caused by dehydrofluorination processes and high irradiation doses, respectively, are avoided, showing the need for facile approaches to chemically crosslink PVDF. Recently, we showed that VDF can be copolymerized using cheap vinyl acetate (VAc) monomers followed by the successful hydrolysis to vinyl alcohol (VA), yielding ferroelectric poly(VDF-co-VA) copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental legislations pointed the coating industries to consider replacement options of these toxic and hazardous materials with nontoxic materials in the coating system. Different anticorrosion coating materials has been reported in the literature for metal protection . Among them graphene has attracted a lot of attention due to its excellent properties like high surface area, impermeable nature, and high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%